Antipyretic Medication Exposures Among Young Children Reported to US Poison Centers, 2000-2015. (March 2018) - Rakowsky, Sofia; Spiller, Henry A.; Casavant, Marcel J.; Chounthirath, Thiphalak; Hodges, Nichole L.; Kim, Eun Hye; Smith, Gary A.
This study used the National Poison Data System database to retrospectively analyze the characteristics and medical outcomes of exposures to antipyretic medications involving children younger than 6 years in the United States. From 2000 through 2015, United States Poison Control Centers recorded an average of 74 387 antipyretic exposures annually among children younger than 6 years. Most exposures involved ibuprofen (55.1%) or acetaminophen (40.1%). From 2000 to 2009, the number of exposures increased by 73.0%, followed by a 25.2% decrease from 2009 to 2015. Children exposed to acetaminophen had 1.98 times higher odds of a serious medical outcome compared with those exposed to ibuprofen. Although generally safe at the correct dosage, antipyretic exposures continue to cause pediatric morbidity and, in rare cases, death. Prevention efforts should focus on reducing child access; educating caregivers about the potential dangers of antipyretics; and discouraging their use, except when needed to improve a child's comfort.